MINIMIZAÇÃO DE IMPACTOS AMBIENTAIS NEGATIVOS DO DESCARTE INCORRETO DE ÓLEO RESIDUAL DE FRITURA - RODRIGUES, Maria Eduarda Morais; ANDRADE, Livia Kethilen de Matos; COSTA e SILVA, Rosangela Maria Ferreira da; KONRADT-MORAES, Leila Cristina (ANAIS DO ENIC, 2024)
-